Impact of the T-wave characteristics on distinguishing arrhythmogenic right ventricular cardiomyopathy from healthy children. (15th January 2021) - Imamura, Tomohiko; Sumitomo, Naokata; Muraji, Shota; Yasuda, Kazushi; Nishihara, Eiki; Iwamoto, Mari; Tateno, Shigeru; Doi, Shozaburo; Hata, Tadayoshi; Kogaki, Shigetoyo; Horigome, Hitoshi; Ohno, Seiko; et al.
Abstract: Background: T-wave inversion (TWI) is not considered useful for diagnosing pediatric arrhythmogenic right ventricular cardiomyopathy (ARVC), because right precordial TWI in ARVC resembles a normal juvenile pattern. Objectives: The aims of this study were to clarify the electrocardiographic (ECG) characteristics of pediatric ARVC to distinguish those patients from healthy children. Methods: Between 1979 and 2017, 11 ARVC patients under 18 years old were registered and compared with school screening ECGs from 48, 401 healthy children. Results: The mean age at the first arrhythmic event or diagnosis was 13.3 ± 4.7 years. Nine patients were asymptomatic initially and were found by ECG screening, but 6 developed severe symptoms during the follow-up. Healthy children had a normal juvenile pattern, while ARVC children, especially symptomatic patients, had a significant tendency to have inferior and anterior TWI. The phenomenon of T-wave discontinuity (TWD) in which the TWI became deeper from V1 to V3 and suddenly turned positive in V5 was significantly more frequent in ARVC (60%) than healthy children (0.55%). Anterior TWI and TWD were also significantly more frequent in those who developed severe symptoms. The sensitivity and specificity of TWD were 60% (95% CI, 31–83%), and 99% (95% CI, 99–99%) to distinguish ARVC from healthy children, as well as 100% (95% CI, 71–100%) and 80% (95% CI, 51–80%), respectively, to predict severe symptoms in the future. Conclusions: The ECG is useful to distinguish ARVC children, even in the early phase. Anterior TWI and TWD could detect ARVC children and to predict the possible serious conditions. Highlights: This study clarified the frequency of T-wave inversion (TWI) in a large cohort of healthy children. T-wave discontinuity (TWD), as well as TWI in the inferior and anterior leads could differentiate ARVC children. TWD and anterior TWI are possible signs to predict a serious prognosis in the future. ARVC children tend not to have VTs but have PVCs and late potentials.